Kajian Awal Pengembangan Media Pembelajaran Berbasis Digital Untuk Pelajaran Biologi Di SMAN 2 Siak Hulu - Salsa Belia Ayu Tryani; Nurul Fauziah; Nurkhairo Hidayati (CV. SINAR HOWUHOWU, 2026)
The development of digital technology has had a significant impact on the field of education, particularly in Biology learning at the senior high school level, which involves many abstract concepts and requires strong visualization. Digital-based learning media have become one of the solutions to improve the quality of learning. This study aims to analyze the initial needs for the development of digital-based learning media in Biology subjects at SMAN 2 Siak Hulu. The research method used was descriptive quantitative. The research population consisted of eleventh-grade students, with a sample of four students selected using simple random sampling techniques. Data collection techniques included interviews and needs assessment questionnaires. The data were analyzed descriptively using quantitative methods by converting Likert scale scores into percentages. The results showed an average score of 79.44%, categorized as strongly agree, indicating that students have a high need for digital learning media to enhance learning interest, conceptual understanding, and the overall effectiveness of Biology learning.